COMMUNITY-BASED HYPERTENSION CONTROL PROGRAM IN RT 01 RW 01 JUMERTO VILLAGE, PATRANG DISTRICT, JEMBER REGENCY - Tantut Susanto; Yuzqi Rizqullah; Iis Safira Ariviana; Yulia Aisyah Nuribu; Risha Putri Mahrdika (UNUSA Press, 2022)
Productive age is a risk group that is prone to hypertension and hypertension increases with age. Management of hypertension plays a role in maintaining the stability of the patient's medical condition and slowing the occurrence of complications. However, the implementation of the hypertension disease management program has not been carried out optimally. This research was carried out quantitatively, with a quasi-experimental type of research using one-group pretest-posttest design approach. Activities were carried out in four stages, namely situation analysis, plan formulation, implementation, and monitoring evaluation. Evaluation of systolic and diastolic blood pressure and knowledge of participants was done before and after the program. The intervention results showed that there were significant differences in systolic, diastolic blood pressure, and public knowledge before and after the program (p<0.005). Community based hypertension management programs have proven to be effective in increasing the knowledge and clinical conditions of people with hypertension. Therefore, to increase knowledge, attitudes, and skills to control hypertension and support are needed by health workers, cadres and families.